2017
DOI: 10.3892/mmr.2017.8282
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-103 suppresses glioma cell proliferation and invasion by targeting the brain-derived neurotrophic factor

Abstract: Glioma is the most common and aggressive of malignant brain tumours. MicroRNAs (miRNAs/miRs) are involved in tumour development of various human cancers, including glioma. Therefore, miRNAs may have potential tumour diagnostic, prognostic and therapeutic values in human glioma. miR‑103 is abnormally expressed in various human cancer types. However, the detailed expression pattern, biological functions and underlying molecular mechanism of miR‑103 in glioma remain unclear. Therefore, the present study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
4
12
1
Order By: Relevance
“…ATF4, activating transcription factor 4; BDNF, brain-derived neurotrophic factor; ELISA, enzyme-linked immunosorbent assay; P2X4R, purinergic receptor P2X 4; siRNA, small interfering RNA; TrkB, Trk receptor tyrosine kinases BDNF expression at mRNA and protein levels were markedly increased in glioma tissues; moreover, decreased BDNF expression by miR-103 inhibits glioma cell proliferation and invasion. 29 Consistent with these reports, our study confirmed that P2X4R silence blocked BDNF/TrkB expression and plays inhibitory role in glioma cell growth. We also confirmed that BDNF overexpression increased TrkB expression compared with P2X4R silence group; however, TrkB overexpression has no obvious effects on BDNF expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ATF4, activating transcription factor 4; BDNF, brain-derived neurotrophic factor; ELISA, enzyme-linked immunosorbent assay; P2X4R, purinergic receptor P2X 4; siRNA, small interfering RNA; TrkB, Trk receptor tyrosine kinases BDNF expression at mRNA and protein levels were markedly increased in glioma tissues; moreover, decreased BDNF expression by miR-103 inhibits glioma cell proliferation and invasion. 29 Consistent with these reports, our study confirmed that P2X4R silence blocked BDNF/TrkB expression and plays inhibitory role in glioma cell growth. We also confirmed that BDNF overexpression increased TrkB expression compared with P2X4R silence group; however, TrkB overexpression has no obvious effects on BDNF expression.…”
Section: Discussionsupporting
confidence: 91%
“…28,29 There has ample evidence indicated that TrkB is a receptor of BDNF and play roles in the action of BDNF. 29 Consistent with these reports, our study confirmed that P2X4R silence blocked BDNF/TrkB expression and plays inhibitory role in glioma cell growth. A, ATF4 expression in U87 and T98 cells were determined by Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the role of BDNF/TrkB/PI3K/Akt signal, we focused on this signal as the underlying mechanism of AG1601 anticancer effects on glioma. Some studies also showed that the recombinant mature BDNF protein, as an activator of BDNF/TrkB signal, could promote the proliferation of glioma cells . Our study also showed that BDNF reversed the inhibitory effects of AG1601 on proliferation of C6 cells (Figure A).…”
Section: Discussionsupporting
confidence: 67%
“…Some studies also showed that the recombinant mature BDNF protein, as an activator of BDNF/TrkB signal, could promote the proliferation of glioma cells. 8,26,27 Our study also showed that BDNF reversed the inhibitory effects of AG1601 on proliferation of C6 cells ( Figure 3A). BDNF also resisted C6 cell apoptosis induced by AG1601.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation